Kekuatan Mengikat Sumpah Adat Dalam Penyelesaian Sengketa Tanah - Siti Rahima Tuahena; Adonia Ivone Laturette; Barzah Latupono (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The indigenous peoples of the Negeri of Pelauw, Haruku Island District, Central Maluku Regency, recognize the customary oath as a customary land dispute resolution system.Purposes of the Research: How is the power to bind the customary oath for the parties in resolving land disputes in the State of Pelauw.Methods of the Research: This study uses empirical legal research with a sociological juridical approach. Research data sources include primary data sources, secondary data sources, and tertiary data sources. The data collection technique was obtained by interviewing the parties directly in the field, then the data was processed using qualitative descriptive analysis.Results of the Research: The results obtained are the strength of binding customary oaths as an alternative dispute resolution in resolving land disputes in the State of Pelauw, namely binding the parties to the dispute even though the decision is made by the Government of the State of Pelauw represented by religious leaders in this case the Imam of the State Mosque of Pelauw in oral form but bound with the disputing parties, even the decisions of the customary oath to their future generations. Based on the observations that the author made at the time of the research, the parties who have resolved disputes through customary oaths from the past until now have not complained because the decision of this customary oath is final.